2011
DOI: 10.1371/journal.pone.0027991
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Lumbar Facet Joint Injection: A Prospective Triple Cross-Over Study

Abstract: The diagnosis “lumbar facet syndrome” is common and often indicates severe lumbar spine surgery procedures. It is doubtful whether a painful facet joint (FJ) can be identified by a single FJ block. The aim of this study was to clarify the validity of a single and placebo controlled bilateral FJ blocks using local anesthetics. A prospective single blinded triple cross-over study was performed. 60 patients (31 f, 29 m, mean age 53.2 yrs (22–73)) with chronic low back pain (mean pain persistance 31 months, 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 66 publications
0
28
0
8
Order By: Relevance
“…A crossover study evaluating the accuracy of diagnostic intra-articular facet blocks found no significant difference in positive rates between anesthetic, placebo, and sham injections. 97 Intra-articular steroid injections are sometimes used to treat cervical facet joint pain, but the technical failure rate is high, the only controlled trial evaluating steroid injections found no benefit, 98 and most systematic reviews have concluded that these injections are ineffective. 91 Clinical studies have found C2-3 and C5-6 to be the most commonly symptomatic levels, 99 100 whereas r adiological studies have found C3-4, C4-5, and C2-3 A hallmark of myofascial pain is the presence of palpable trigger points, which are taut muscle bands that refer pain in a defined pattern spontaneously or after stimulation, although their clinical relevance is controversial.…”
Section: Myofascial Painmentioning
confidence: 99%
“…A crossover study evaluating the accuracy of diagnostic intra-articular facet blocks found no significant difference in positive rates between anesthetic, placebo, and sham injections. 97 Intra-articular steroid injections are sometimes used to treat cervical facet joint pain, but the technical failure rate is high, the only controlled trial evaluating steroid injections found no benefit, 98 and most systematic reviews have concluded that these injections are ineffective. 91 Clinical studies have found C2-3 and C5-6 to be the most commonly symptomatic levels, 99 100 whereas r adiological studies have found C3-4, C4-5, and C2-3 A hallmark of myofascial pain is the presence of palpable trigger points, which are taut muscle bands that refer pain in a defined pattern spontaneously or after stimulation, although their clinical relevance is controversial.…”
Section: Myofascial Painmentioning
confidence: 99%
“…Die Genese von Lumbalgien und Lumboischialgien ist oftmals komplex und in praktisch allen Fällen multifaktoriell. Die Erstbeschreibung lumbaler Facettengelenke als mögliche schmerzauslösende Ursache erfolgte bereits 1911 durch Goldthwait [1,2], Ghormley beschrieb 1933 den Begriff des Facettengelenks-Syndroms als Kombination aus klinischer Symptomatik und einer Degeneration der lumbalen Facettengelenke [3]. Nach der Einführung des Novokains in 1905 beschrieben eine Reihe von Autoren unterschiedliche Injektionen im Bereich der Wirbelsäule zur Schmerzprovokation als auch -reduktion [4].…”
Section: Historischer üBerblickunclassified
“…In der Betrachtung der Evidenz für eine diagnostisch positive Facettengelenksinfiltration der Lendenwirbelsäule ist allen Studienbedingungen gemein das das Ausmaß der Schmerzreduktion das maßgebliche Beurteilungskriterium darstellt. Darüber hinaus fehlt ein Gold-Standard [2].…”
Section: Diagnostische Facettengelenksinfiltrationen: Lendenwirbelsäuleunclassified
See 2 more Smart Citations